Integrated Synthesis of Calcitriol and 26,27-Hexadeutero Calcitriol - Tang, Fei; Cui, Feng; Yu, Gang; Qi, Lichun; Zhang, Qingwen (Pharmaceutical Fronts, 2024)
Calcitriol (1α,25-dihydroxyvitamin D3, 1), a classical vitamin D drug, is indicated primarily in the treatment of patients with postmenopausal osteoporosis and renal osteodystrophy. In this study, a practical synthesis of calcitriol (1), from readily available commercial vitamin D2 (5) via hub intermediate 18, has been accomplished in 9% overall yield. This semi-synthetic process embedded four prominent elements of vitamin D chemistry: (1) cheletropic sulfur dioxide (SO2) adduction for the isomerization of the characteristic triene from (5Z,7E) to (5E,7E), or for the protection of the triene for selective ozonolysis of the side chain, and cheletropic extrusion of SO2 from the adduct in ethanolic sodium bicarbonate to retrieve the triene; (2) direct, regio- and stereoselective 1α-hydroxylation of 3β-TBS-protected (5E)-calciferol intermediate 19 using selenium dioxide in the presence of N-methylmorpholine N-oxide as a re-oxidant in a hot mixture of methylene chloride and methanol; (3) nickel(0)-mediated conjugate addition of the 22-iodide 23 to electron-deficient ethyl acrylate followed by Grignard reaction with methylmagnesium bromide to construct the calcitriol side chain; and (4) triplet-sensitized photoisomerization of 26 to access the bioactive (5Z,7E)-triene in calcitriol (1). The high-performance liquid chromatography purities of batches of the synthesized calcitriol (1) were consistently more than 99.9%, with related substances listed in the USP 2023 and EP 11.0 well controlled. This robust process proved amenable to pilot scale-up and industrial production. 26,27-Hexadeutero calcitriol (4), a deuterium-labeled calcitriol derivative, is useful as the internal standard in the bioanalysis for the quantification of calcitriol in serum. 4 was efficiently synthesized in an integrated manner from hub intermediate 18 in 48% yield.
Keywords: calcitriol; deuterium-labeled calcitriol; vitamin D; practical synthesis; related substances